ALGORITMA KRUSKAL UNTUK MENYELESAIKAN MASALAH OPTIMASI DISTRIBUSI JARINGAN LISTRIK DI PLN UP3 CIMAHI - Sartika, Euis; Lusiani, Anie; Suhartini, Ida; Nuryati, Neneng (EPSILON: JURNAL MATEMATIKA MURNI DAN TERAPAN (EPSILON: JOURNAL OF PURE AND APPLIED MATHEMATICS), 2024)
The addition of new houses in the Kota Mas Cimahi housing complex has triggered an increase in the need for electricity distribution installations. To optimize the electricity distribution network, in this case minimizing the installation of electrical cables, an application is needed that can optimize the installation of electrical cables, namely the Kruskal algorithm which is an algorithm for finding the minimum spanning tree value on a weighted graph. In this study, two methods will be used, namely the manual method and the POM-QM for Windows software to help solve the minimum spanning tree problem. This study's goal is to identify the Kota Mas Cimahi housing complex's energy distribution network model's graph structure and determine a minimum spanning tree solution with POM-QM for Windows software and the Kruskal technique done by hand. In order to gather data for this study, PLN was the primary and secondary source Cimahi UP3. The distribution data for the electricity cable network is arranged in the form of a network image. By representing the electricity distribution network in the form of a graph, the minimum spanning tree is then obtained, and the solution to the MST (Minimum Spanning Tree) problem uses the Kruskal algorithm and TORA software. The results of the study showed that the minimum spanning tree cable length which was originally 1424.61 meters, after using the Kruskal algorithm manually became 1258.05 meters and also by using the POM-QM for Windows software obtained a minimum result of 1258.05 meters, so it can be concluded that there is a cable length efficiency of 11.69%.